T2-Weighted Dixon Turbo Spin Echo for Accelerated Simultaneous Grading of Whole-Body Skeletal Muscle Fat Infiltration and Edema in Patients With Neuromuscular Diseases. Issue 4 (July 2018) - Schlaeger, Sarah; Klupp, Elisabeth; Weidlich, Dominik; Cervantes, Barbara; Foreman, Sarah C.; Deschauer, Marcus; Schoser, Benedikt; Katemann, Christoph; Kooijman, Hendrik; Rummeny, Ernst J.; Zimmer, Claus; Kirschke, Jan S.; et al.
Abstract : Objective: The assessment of fatty infiltration and edema in the musculature of patients with neuromuscular diseases (NMDs) typically requires the separate performance of T1 -weighted and fat-suppressed T2 -weighted sequences. T2 -weighted Dixon turbo spin echo (TSE) enables the generation of T2 -weighted fat- and water-separated images, which can be used to assess both pathologies simultaneously. The present study examines the diagnostic performance of T2 -weighted Dixon TSE compared with the standard sequences in 10 patients with NMDs and 10 healthy subjects. Methods: Whole-body magnetic resonance imaging was performed including T1 -weighted Dixon fast field echo, T2 -weighted short-tau inversion recovery, and T2 -weighted Dixon TSE. Fatty infiltration and intramuscular edema were rated by 2 radiologists using visual semiquantitative rating scales. To assess intermethod and interrater agreement, weighted Cohen's κ coefficients were calculated. Results: The ratings of fatty infiltration showed high intermethod and high interrater agreement (T1 -weighted Dixon fast field echo vs T2 -weighted Dixon TSE fat image). The evaluation of edematous changes showed high intermethod and good interrater agreement (T2 -weighted short-tau inversion recovery vs T2 -weighted Dixon TSE water image). Conclusions: T2 -weighted Dixon TSE imaging is an alternative for accelerated simultaneous grading of whole-body skeletal muscle fat infiltration and edema in patients with NMDs.